Extended cheese whey fermentation produces a novel casein-derived antibacterial polypeptide that also inhibits gelatinases MMP-2 and MMP-9 - Santos, Maria Isabel (2021)
Our previous works produced a whey fermentation methodology that yielded antibacterial activity and potential inhibition of matrix metalloproteases (MMP)-2 and -9. Here, we evaluated if these activities were due to fermentation-produced peptides. Prolonged fermentation was carried out in the presence of our specific lactic acid bacteria (LAB) consortium. LAB fermentation yielded a total of 11 polypeptides, which were predominantly produced after 6 days of fermentation. One which was derived from beat casein presented a particularly high antibacterial activity against food pathogenic bacteria and was more effective than standard food disinfectants. This polypeptide was further studied and was also found to be active against several strains of pathogenic bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), in a dose-dependent manner. It also inhibited MMP-2 and MMP-9 whilst reducing HT29 cancer cell migration in vitro. Overall, this novel whey-derived polypeptide presents dual antibacterial and anti-inflammatory activity, revealing a strong potential to be used in functional foods or as a nutraceutical. Its identification and further characterization can open novel perspectives in the field of preventive/curative diets related to gut microbiota, gut inflammation, and cancer prevention, particularly if used in in vivo studies